High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Experimental Challenge of Chinook Salmon ( Oncorhynchus tshawytscha ) With Tenacibaculum maritimum and Tenacibaculum dicentrarchi Fulfils Koch's Postulates - Karthiga Kumanan; Jeremy Carson; Ryan B. J. Hunter; Anne Rolton; Ulla von Ammon; Chaya Bandaranayake; Connie Angelucci; Richard N. Morrison; Seumas P. Walker; Jane E. Symonds; Kate S. Hutson (Journal of Fish Diseases, 2025)
The bacterial skin disease tenacibaculosis, caused by Tenacibaculum species, affects numerous economically important marine fish, including salmonids. This study reports the ability of three Tenacibaculum maritimum strains, belonging to different molecular O‐AGC types, and a single Tenacibaculum dicentrarchi strain to induce tenacibaculosis in farmed Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792) in Aotearoa New Zealand. Naïve Chinook salmon were exposed to T. maritimum (2 × 10 8 cells/mL) and T. dicentrarchi (2 × 10 7 cells/mL) by immersion using natural seawater. Clinical signs of tenacibaculosis were apparent in all T. maritimum strains used in the challenged fish. Of these, 100% of the fish challenged with O‐AGC Type 2‐1 and Type 3‐2 strains became moribund, whereas only 60% of the O‐AGC Type 3‐0 challenged fish became moribund. Fish exposed to T. dicentrarchi showed more severe symptoms, exposing musculature in 51% of the challenged population, with 28% of fish becoming moribund. Gross pathological signs of fin rot, scale loss, skin ulcers and haemorrhagic skin spots were observed for both Tenacibaculum species and were consistent with those observed on farmed fish. Pure T. maritimum and T. dicentrarchi cultures were reisolated from epidermal damage of challenged fish. Tenacibaculum species was not isolated from the anterior kidney of affected fish, which indicates no systemic infection in Chinook salmon.

Optimising Outbreak Investigation, Surveillance and Discovery of Pathogens in Aquaculture Using Unbiased Metatranscriptomics - Vincenzo A. Costa; Richard J. Whittington; Charles Caraguel; Joy A. Becker; Kerrie E. Wiley; Christine Huynh; Jeremy Carson; Francisca Samsing (Reviews in Aquaculture, 2025)
Emerging infectious diseases are a major threat to global aquaculture production and are projected to increase in frequency due to anthropogenic stressors and climate change. Our ability to screen the global aquatic ‘infectome’ is dramatically improving through unbiased metatranscriptomic (i.e., total RNA) sequencing. Despite recent advances in molecular diagnostics and next‐generation sequencing, outbreak investigation in aquaculture often encounters limitations due to the targeted nature of conventional techniques, which may only capture a small portion of the diverse array of disease‐causing agents present in nature, sometimes requiring years to resolve. Here, we propose that unbiased metatranscriptomic sequencing serves as a cost‐effective and powerful technique for characterising pathogens during disease outbreaks and in surveillance programmes. In doing so, we offer a diagnostic framework to mitigate infectious disease threats to global aquaculture. We emphasise the importance of combining rapid metatranscriptomics with traditional techniques for a holistic examination of the causes of unknown aetiologies in aquatic animals, and how it can be used to examine host responses in parallel with pathogen discovery. We suggest that the integration of metatranscriptomics into aquaculture will require upskilling, proficiency testing, user‐friendly bioinformatic tools and open data sharing. Furthermore, it is essential to establish a reporting framework—with analytical guidelines—that ensures the protection of animal industries while safeguarding trade interests.

Serological and molecular typing of Tenacibaculum maritimum from New Zealand farmed salmon, Oncorhynchus tshawytscha - Karthiga Kumanan; Lizenn Delisle; Connie Angelucci; Ryan B.J. Hunter; Oleksandra Rudenko; Jeremy Carson; Richard N. Morrison; Andrew C. Barnes; Kate S. Hutson (Aquaculture, 2024)

Basal forebrain functional connectivity as a mediator of associations between cardiorespiratory fitness and cognition in healthy older women - Junyeon Won; Laszlo Zaborszky; Jeremy J. Purcell; Sushant M. Ranadive; Rodolphe J. Gentili; J. Carson Smith (Brain Imaging and Behavior, 2023)

Cold temperature stress and damaged skin induced high mortality in barramundi ( Lates calcarifer ) challenged with Vibrio harveyi - Francisca Samsing; William Zhang; Ruth N. Zadoks; Richard Whittington; Carola Venturini; Carla Giles; Jeremy Carson; Joy A. Becker (Journal of Fish Diseases, 2023)
Most diseases in aquaculture are caused by opportunistic pathogens. One of them, Vibrio harveyi , is a widespread Gram‐negative bacterium that has become an important pathogen of aquatic species in marine environments. Here, we propose the use of the causal pie model as a framework to conceptualize the causation of vibriosis in juvenile barramundi ( Lates calcarifer ) and to establish an effective challenge model. In the model, a sufficient cause, or the causal pie, is a constellation of component causes that lead to an outcome (e.g. vibriosis). In the pilot study, a high cumulative mortality (63.3% ± 10.0%, mean ± SE) was observed when V. harveyi was administered by intraperitoneal injection using a high challenge dose [10 7 colony‐forming units (CFU) fish −1 ], but low or no mortality was observed in fish subject to cold stress or fish with intact skin when challenged by immersion. We, therefore, tested the use of a skin lesion (induced with a 4‐mm biopsy punch) combined with cold temperature stress to induce vibriosis following the causal pie model. After challenge, fish were immediately subject to cold stress (22°C) or placed at an optimal temperature of 30°C. All groups were challenged with 10 8 CFU mL −1 for 60 min. A considerably higher mortality level (72.7% ± 13.9%) was observed in fish challenged with both a skin lesion and cold stress compared with mortality in fish only having a skin lesion (14.6% ± 2.8%). V. harveyi was re‐isolated from all moribund fish and was detected by species‐specific real‐time PCR in gills, head kidney and liver, regardless of challenge treatment confirming vibriosis as the cause of disease. Parenchymal tissues had histopathological changes consistent with vibriosis. Whole‐genome sequence (WGS) is provided for the Vibrio harveyi isolate examined in this study. Overall, the causal pie model was a useful framework to conceptualize the design of the experimental challenge model, in which both cold stress and skin damage were identified as component causes of vibriosis with high mortality. This conceptual framework can be applied to other opportunistic pathogens in aquaculture or to the study of co‐infections in fish.

Genetic and genomic analyses of resistance to yersiniosis in Atlantic salmon (Salmo salar) assessed by tank challenge - Richard S. Taylor; Roberto Carvalheiro; Amanda L. Patchett; Klara L. Verbyla; Jeremy Carson; James W. Wynne; Brad S. Evans; Curtis E. Lind; Harry King (Aquaculture, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Seawater transmission and infection dynamics of pilchard orthomyxovirus (POMV) in Atlantic salmon ( Salmo salar ) - Francisca Samsing; Megan Rigby; Hedda K. Tengesdal; Richard S. Taylor; Daniela Farias; Richard N. Morrison; Scott Godwin; Carla Giles; Jeremy Carson; Chloe J. English; Roger Chong; James W. Wynne (Journal of Fish Diseases, 2021)
The Tasmanian salmon industry had remained relatively free of major viral diseases until the emergence of pilchard orthomyxovirus (POMV). Originally isolated from wild pilchards, POMV is of concern to the industry as it can cause high mortality in farmed salmon ( Salmo salar ). Field observations suggest the virus can spread from pen to pen and between farms, but evidence of passive transmission in sea water was unclear. Our aim was to establish whether direct contact between infected and naïve fish was required for transmission, and to examine viral infection dynamics. Atlantic salmon post‐smolts were challenged with POMV by either direct exposure via cohabitation or indirect exposure via virus‐contaminated sea water. POMV was transmissible in sea water and direct contact between fish was not required for infection. Head kidney and heart presented the highest viral loads in early stages of infection. POMV survivors presented low viral loads in most tissues, but these remained relatively high in gills. A consistent feature was the infiltration of viral‐infected melanomacrophages in different tissues, suggesting an important role of these in the immune response to POMV. Understanding POMV transmission and host–pathogen interactions is key for the development of improved surveillance tools, transmission models and ultimately for disease prevention.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)